Governors and general captains of the State of Maranhão and Grão-Pará and of the State of Grão-Pará and Maranhão (1702 to 1780): comparative careers - Santos, Fabiano Vilaça dos (Revista Crítica Histórica, 2018)
This article presents a synthesis of research notes on the careers of the governors and captains-generals of the State of Maranhão and Grão-Pará (1702-1751) and of the State of Grão-Pará and Maranhão (1751-1780), in a comparative perspective. The origin and social quality of 12 agents, their formation, experiences in the service to the monarchy, as well as the governmental circuits that they have covered in the governance of the Empire are characterized. It is intended to demonstrate the existence of similarities and differences in the social profiles, career and circulation of the colonial administrators of the State of Maranhão and Grão-Pará and of the State of Grão-Pará and Maranhão, from the beginning to the second half of the eighteenth century, and in a subsequent phase corresponding roughly to the Pombaline period. Although focused on the study of government careers, this work seeks to contribute to a review of the administrative history of the captaincies of Pará and Maranhão at different moments of their political configuration, with emphasis on government and governors. Keywords: Governors and general captains; State of Maranhão and Grão-Pará/State of Grão-Pará and Maranhão; Careers